Зв’язок продуктивності цвітіння сортів Cymbidium hybridum hort. з їх регенераційною та асиміляційною здатністю - Zaimenko, N.V.; Cherevchenko, Т.M.; Lavrentyeva, A.N. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
Relation between flower productivity of Cymbidium hybridum hort. varieties and their regenerative ability, morpho- anatomical indices of leaves, and content of photosynthetic pigments has been determined.